Facing the Khmer Rouge : A Cambodian Journey - Yimsut, Ronnie, 1961- (Book collections on Project MUSE., 2011)
As a child growing up in Cambodia, Ronnie Yimsut played among the ruins of the Angkor Wat temples, surrounded by a close-knit community. As the Khmer Rouge gained power and began its genocidal reign of terror, his life became a nightmare. In this stunning memoir, Yimsut describes how, in the wake of death and destruction, he decides to live. Facing the Khmer Rouge shows Ronnie Yimsut's personal quest to rehabilitate himself, make a new life in America, and then return to Cambodia to help rebuild the land of his birth.